2013
DOI: 10.1515/hsz-2013-0206
|View full text |Cite
|
Sign up to set email alerts
|

Roasting and lipid binding provide allergenic and proteolytic stability to the peanut allergen Ara h 8

Abstract: Ara h 8 is the peanut allergen homologous to the birch pollen allergen Bet v 1. Because Bet v 1 has been shown to bind lipophilic ligands, the aim of this investigation was to determine the impact of lipid binding and roasting on the Ara h 8 structure and their influences on allergenicity. For the characterization of natural Ara h 8 (nAra h 8) from roasted and unroasted peanuts, circular dichroism spectroscopy, hydrophobic binding assay, immunohistochemistry, and immunoblot with sera of peanut allergic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 51 publications
(65 reference statements)
1
56
1
Order By: Relevance
“…Due to their high polyunsaturated fatty acid content peanuts suffer lipid oxidation,during storage or roasting. Allergenicity could change if new protein-lipid complexes or changes in protein structures occur when the lipid hidroperoxides formed attack the proteins (74). …”
Section: Lipid Cargo May Affect Allergenicitymentioning
confidence: 99%
“…Due to their high polyunsaturated fatty acid content peanuts suffer lipid oxidation,during storage or roasting. Allergenicity could change if new protein-lipid complexes or changes in protein structures occur when the lipid hidroperoxides formed attack the proteins (74). …”
Section: Lipid Cargo May Affect Allergenicitymentioning
confidence: 99%
“… 71 Food allergens of the Bet v 1–like family generally are susceptible to pepsin digestion and instable to thermal processing and usually provoke only mild allergic symptoms. A recent study on Ara h 8, the Bet v 1 homolog from peanut, showed that roasting of peanuts can dramatically increase not only its thermal stability but also protect the allergen against proteolysis by gastrointestinal enzymes 18 . Ara h 8 isolated from roasted peanuts showed enhanced IgE reactivity and was also recognized by more sera from patients with peanut allergy compared with Ara h 8 isolated from raw peanuts.…”
Section: Interaction Of Lipids and Food Allergensmentioning
confidence: 99%
“…The authentic structure of Ara h 8.0201 was confirmed by trypsin fingerprinting of isolated nAra h 8. In accordance with the Bet v 1 it was possible to show experimentally that Ara h 8 contains a hydrophobic region [68] in which lipids bind, which, according to preliminary experiments, may prevent the molecule from gastric digestion [68] . All in all these findings spotlight the significance of lipid-protein-(allergen) interaction.…”
Section: Ara H 5 and Ara Hmentioning
confidence: 65%